2019
DOI: 10.1186/s40164-019-0133-1
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax with azacitidine targets refractory MDS but spares healthy hematopoiesis at tailored dose

Abstract: Patients with Myelodysplastic Syndromes (MDS) and secondary Acute Myeloid Leukemia (sAML) have a very poor prognosis after failure of hypomethylating agents (HMA). Stem cell transplantation is the only effective salvage therapy, for which only a limited number of patients are eligible due to age and comorbidity. Combination therapy of venetoclax and azacitidine (5-AZA) seems to be a promising approach in myeloid malignancies, but data from patients with HMA failure are lacking. Furthermore, a considerable conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…In different clinical trials administration of venetoclax led to neutropenia, thrombocytopenia, tumor lysis syndrome, and neutropenic fever [ 33 , 34 ]. Meanwhile, treatment of healthy bone marrow mononuclear cells with venetoclax reduced their cell viability and this toxic effect further increased by the addition of 5-azacitidine [ 35 ]. Furthermore, Ko et al claimed the higher sensitivity of healthy CD34+ cord blood stem cells to venetoclax compared to CML cells [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In different clinical trials administration of venetoclax led to neutropenia, thrombocytopenia, tumor lysis syndrome, and neutropenic fever [ 33 , 34 ]. Meanwhile, treatment of healthy bone marrow mononuclear cells with venetoclax reduced their cell viability and this toxic effect further increased by the addition of 5-azacitidine [ 35 ]. Furthermore, Ko et al claimed the higher sensitivity of healthy CD34+ cord blood stem cells to venetoclax compared to CML cells [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the MLL gene can recombine with more than 60 partners to acquire abnormal gain-of-function effects on aberrant epigenetic modification and proto-oncogene activation, as a result triggering dysregulated increased expression of the clustered homeobox A (HOXA) genes, which results in limitless self-renewal capacity necessary for leukemia initiation and propagation [3]. Hematopoietic malignancy caused by MLL translocation, especially MLL-AF9, has been reported to have an apex self-renewal to generate more distinct self-renewing progenitor-like leukemia cells that are resistant to chemotherapy and are responsible for relapse [6,[8][9][10]. Persistence of MLL leukemia clones after treatment including available cell cycle-based or signaling protein-targeted therapies is the critical factor for unsatisfactory treatment outcome [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis furthermore confirmed the reduction in Mcl1 protein levels in both OTSSP167 and combo treated cells and the further increase in cleaved caspase-3 levels in the combo treated cells. Importantly, it has been reported that a concentration of 1 μM venetoclax corresponds to the clinically recommended dose of 400 mg per day in patients 57,58 . For our in vitro combination experiments, we used sub-optimal concentrations of venetoclax well below 1 μM.…”
Section: Discussionmentioning
confidence: 99%